2008
DOI: 10.1063/1.2814250
|View full text |Cite
|
Sign up to set email alerts
|

Negative-ion source applications (invited)

Abstract: In this paper heavy negative-ion sources which we developed and their applications for materials science are reviewed. Heavy negative ions can be effectively produced by the ejection of a sputtered atom through the optimally cesiated surface of target with a low work function. Then, enough continuous negative-ion currents for materials-science applications can be obtained. We developed several kinds of sputter-type heavy negative-ion sources such as neutral- and ionized-alkaline metal bombardment-type heavy ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…20,21 Tsuji et al 22,23 found that a better adhesion of rat mesenchymal stem cells could be obtained by C-ion implantation at a dose of 3×10 15 ions/cm 2 on the surface of silicone rubber and that when this was done using raster graphics, cell growth could be induced along the direction of the pattern. In this study, we found that dermal fibroblasts grow faster and in a more orderly manner in the case of a silicone rubber surface modified with both microgrooves and C-ion implantation; cell adhesion rate was also increased significantly, and there was an increase in the amount of cell adhesion plaque proteins.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Tsuji et al 22,23 found that a better adhesion of rat mesenchymal stem cells could be obtained by C-ion implantation at a dose of 3×10 15 ions/cm 2 on the surface of silicone rubber and that when this was done using raster graphics, cell growth could be induced along the direction of the pattern. In this study, we found that dermal fibroblasts grow faster and in a more orderly manner in the case of a silicone rubber surface modified with both microgrooves and C-ion implantation; cell adhesion rate was also increased significantly, and there was an increase in the amount of cell adhesion plaque proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an ion is a many-electron particle, which represents the abundant varieties of ion species [10][11][12][13][14][15]. For example, many kinds of ions, as well as several charged states of ions, are available.…”
Section: Introductionmentioning
confidence: 99%
“…It represents several features in material processing, one of which is that it can transfer charge, energy and mass employed for material surface treatment. Another feature is that various kinds of species such as atomic, molecular and cluster ions are available [3,4]. In particular, polyatomic ions such as water and alcohol ions contain several kinds of radicals such as hydroxyl and alkyl radicals, and these radicals have an important role in surface modification and chemical erosion of the surface [5,6].…”
Section: Introductionmentioning
confidence: 99%